Development of interactive resume / Tan Phaik See - Tan , Phaik See (2005)
As a fulfillment to our Information Technology Degree Program in University of Malaya, all undergraduate students were required to accomplish a Final Year Thesis Project. Thesis title of my project is Development of Interactive Resume. As for development this project, I would name it Interactive Resume System (IRS). Interactive Resume System (IRS) is a smart web-based system which allows users to going step-by step to generate their resume in an interactive way. The "interactive way" is means to present the user's resume in two ways. First is the common and usual method which resume in paper printing. The second way which is the most modern and attractive approach is to present their resume in a flash scheme. As for the applications development, Visual Basic 6.0, PHP and MySQL will be used in this project. With the IRS, the users will be access the secured services in both easier and convenient fashion. As an overall review, IRS is a meaningful system which providing helps and convenient for the user to develop their interactive resume in no doubt.